(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2025)
This in the article teachers to the news flexibility and this in process used modern methods analysis In the study technology education to the process implementation to do, pedagogical change approaches and flexibility increase effective methods were reviewed. Results shows that flexibility develop for continuous qualification improvement, technological literacy increase and collegial cooperation important importance has. This research modern education system improvement for necessary was methods to illuminate focused.